Recorrências e algumas aplicações em problemas de contagem - SILVA, Paulo Roberto Rêgo da (2020)
Many mathematical problems, in which it is necessary to count certain elements, present themselves in situations that are difficult to solve. We present in this work an alternative way to solve some counting problems that can help to overcome these difficulties. The proposed form addresses a recursive reasoning called mathematical recurrence or, simply, recurrence. This recursive thinking is presented superficially in High School of Basic Education. We will show here some questions that address counting problems and that may seem difficult to be solved at first sight, but that through the perception of a recurrence relationship in the proposed problem, the solution can be easily found. Thus, our main objective is to provide another mathematical tool that will, in some situations, complement the learning about Combinatorial Analysis events, in particular, the counting of certain elements.